Decline of case reports in pathology and their renewal in the digital age: an analysis of publication trends over four decades. Issue 2 (16th December 2022) - Cima, Luca; Pagliuca, Francesca; Torresani, Evelin; Polonia, Antonio; Eloy, Catarina; Dhanasekeran, Venkatesh; Mannan, Rifat; Gamba Torrez, Silvia; Mirabassi, Nicola; Cassisa, Angelo; Palicelli, Andrea; Barbareschi, Mattia
Abstract : Aims: We investigated the trend in case reports (CRs) publication in a sample of pathology journals. Furthermore, we proposed an alternative publishing route through new digital communication platforms, represented by the 'social media case report'. Methods: 28 pathology journals were selected from SCImago database and searched in PubMed to identify the number of published CRs. Four reference decades (1981–2020) were selected. The 5-year impact factor (IF) was retrieved from the Academic Accelerator database. Results: CRs increased during the first three decades (6752, 8698 and 11148, respectively; mean values: 355, 27.3%; 334, 26.4%; 398, 28.8%) as the number of CR-publishing journals (19, 26 and 28, respectively). In the last decade, CRs significantly decreased (9341; mean 334, 23.6%) without variation in the number of CR-publishing journals (28). Half of the journals reduced CRs (from −1.1% to −37.9%; mean decreasing percentage −14.7%), especially if active since the first decade (11/14, 79%); the other half increased CRs (from +0.5% to +34.2%; mean increasing percentage +11.8%), with 8/14 (57%) starting publishing in the first decade. The 5-year IF ranged from 0.504 to 5.722. Most of the journals with IF ≥2 (10/14, 71%) reduced the CRs number, while 71% of journals with IF <2 increased CRs publication (especially journals with IF <1, +15.1%). Conclusions: CRs publication decreased during the last decade, especially for journals which are older or have higher IF. Social media CRs may represent a valid alternative and by using standardised templates to enter all relevant data may be organised in digital databases and/or transformed in traditional CRs.